First record of the genus Dinophasma Uvarov from the Philippines (Phasmatodea: Aschiphasmatidae) - Gottardo, Marco (Zootaxa, 2007)
As presently defined, the genus Dinophasma Uvarov, 1940 (= Dina Redtenbacher, 1906, = Xylobistus Zompro, 2004) includes 8 species (Otte & Brock, 2005), 7 of which are widespread in Borneo and one is represented in India. A study of several unidentified specimens of Philippine Aschiphasmatidae allowed recognition of a single male specimen of Dinophasma that cannot be assigned to any known species. The new species is described and illustrated in the present paper and marks the first record of the genus from the Philippines. An identification key to all species of Dinophasma, revised from that presented by Bragg (2001), is also provided